MIND MAPPING BASED JOYFULL LEARNING TO INCREASE WRITING SKILL - Dayu, Dian Kusuma; Aprilia, Septi (UIN Sunan Kalijaga Yogyakarta, 2022)
This study aims to find out the differences in writing skills in elementary schools by using Mind Mapping based joy full learning models and determining the effectiveness of using Mind Mapping based joy full learning models in Indonesian writing skills. This research method is included in experimental research, which takes two groups as research samples. A quasi-experimental study was conducted on 30 elementary school students randomly assigned to the experimental or control group. The data collection method used is the writing skill test method. Before giving the writing activity, a pre-test was carried out. It continued the writing activity by using the experimental group's mind mapping model based on joyful learning. At the same time, the control class did not receive treatment using this model. Next, a post-test was conducted in both groups to determine the effectiveness of the joyful learning-based mind mapping learning model. The data analysis techniques were validity, reliability, normality, homogeneity, and t-test. Data analysis used the Independent Sample T-Test technique. The Independent sample t-test showed that the experimental group obtained a higher mean score than the control group. The results of this study indicate that T- arithmetic: 2.354> T-table: 2,000. It can be concluded that the teaching system using the Mind Mapping-based Joy full learning models was better than those that did not use the Mind Mapping-based Joyful learning models. The results of the data analysis are Mind Mapping-based joy-full learning models effectively teach Indonesian writing skills in elementary school. The recommendation of this research is for further research to modify the mind mapping learning model based on joyful learning to be more effective in improving writing skills in elementary school students.